2011
DOI: 10.1002/app.34375
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaliphatic epoxy oligosiloxane‐derived hybrid materials for a high‐refractive index LED encapsulant

Abstract: Cycloaliphatic epoxy oligosiloxane resins with a high degree of condensation (>85%) were synthesized by a nonhydrolytic sol–gel reaction using 2‐(3,4‐epoxycyclohexyl)ethyltrimethoxysilane (ECTS), diphenylsilanediol (DPSD), and triphenylsilanol (TPS). Cycloaliphatic epoxy hybrimers with 2 mm thickness fabricated by thermal curing of cycloaliphatic epoxy oligosiloxane resins with a hardener and catalyst were optically transparent (∼90%) with a high refractive index of up to 1.583. The fabricated hybrimers also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 21 publications
(29 reference statements)
1
32
0
Order By: Relevance
“…Recently, we reported an organic/inorganic hybrid material (hybrimer) fabricated by the photocationic polymerization of sol–gel‐derived cycloaliphatic epoxy oligosiloxane (CAEO) resins with a high viscosity. Because of the high transparency, photopatternability, and excellent gas barrier properties, CAEO hybrimers have been used in manifold applications, such as encapsulants for organic light‐emitting diodes 17–19. However, the low photocationic polymerization speed of cycloaliphatic epoxy groups and the limited crosslinking density of CAEO hybrimers, originating from the high viscosity of the CAEO resin, can degrade the basic physical properties of CAEO hybrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported an organic/inorganic hybrid material (hybrimer) fabricated by the photocationic polymerization of sol–gel‐derived cycloaliphatic epoxy oligosiloxane (CAEO) resins with a high viscosity. Because of the high transparency, photopatternability, and excellent gas barrier properties, CAEO hybrimers have been used in manifold applications, such as encapsulants for organic light‐emitting diodes 17–19. However, the low photocationic polymerization speed of cycloaliphatic epoxy groups and the limited crosslinking density of CAEO hybrimers, originating from the high viscosity of the CAEO resin, can degrade the basic physical properties of CAEO hybrimers.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated mechanical stresses may have reduced the overall LED reliability. Bae et al . mentioned that LED encapsulants should have a proper hardness to protect the LED die from the stress shock and humidity corrosion of the LED devices during operation.…”
Section: Resultsmentioning
confidence: 99%
“…[29] The peaks at −57.8 and −67.4 ppm are assigned to the silicon in (R 1 )SiO 3/2 units (R 1 = 3-glycidoxypropyl). [30] Based on the FTIR, 1 H-NMR, and 29 Si-NMR analyses, it can be concluded that PSREA was successfully prepared.…”
Section: Structural Characterization Of Psreamentioning
confidence: 98%